Utilization of Back Movement Technique to Intensity of Low Back Pain in Third Trimester Pregnant Women - Saptyani, Putri Maretyara; Suwondo, Ari; Runjati, Runjati (STRADA : Jurnal Ilmiah Kesehatan, 2020)
One of the discomforts in third-trimester pregnancy is lower back pain.The prevalence of back pain during pregnancy can reach 80%. The study aims to prove the use of back movement technique to decrease the intensity of low back pain in third trimester pregnant women. The study used quasy-experimental, pretest-posttest with control group design. The sample of the study was third-trimester pregnant women with low back pain totaling 40 respondents. The instrument used to measure back pain in pregnancy is the Numeric Rating Scale (NRS). Data analysis used wilcoxon and man-whitney. There was a decrease in intensity of low back pain before treatment by 4.75 cm and after being given a back movement technique of 1.55 cm (p = 0.001). Back movement technique is proven to be more effective in reducing the intensity of low back pain in third-trimester pregnant women.